Towards a sustainable development of retailing in Romania - Viorel Coca; Mihaela Dobrea; Cristinel Vasiliu (Amfiteatru Economic Journal, 2013)
Sustainable development becomes increasingly important in the design of development policies. The economic field, due to the businesses it involves, is regarded as a tool capable of generating social well-being by caring for resource conservation. The retailing is part of this process, playing an important role due to the connection it provides between producers and consumers. The objectives of this study were to highlight the extent to which retailing developed in Romania, to measure the efficiency of firms in the industry and to identify sustainable development practices these firms used. In developing our approach a sample of 12 firms were selected, which were defined as constituting a reference framework based on their size and turnover. Further on, the descriptive research method was used, based on secondary sources of data investigation. After analyzing the data, it was concluded that the retailing sector in Romania is a powerful one, with a market slightly increasing, dominated by trends of concentration and with efficiency in line with the European average. The use of the principles of sustainable development into trade business companies in Romania is low. There is no urge to see these principles as business opportunities and sources of competitiveness.
Keywords: L81; Q01; 330; sustainable development; retailing; environment protection; efficiency; social responsibility